Comparison of in vitro synergistic effect between clarithromycin or azithromycin in combination with amikacin against Mycobacterium intracellulare. (September 2019) - Zhang, Zhijian; Lu, Jie; Du, Yingzhen; Xie, Fei; Wang, Yufeng; Sun, Baojun; Pang, Yu
Highlights: Clarithromycin is more potent than azithromycin in vitro against Mycobacterium intracellulare . Antagonism between azithromycin–amikacin is more frequent in M. intracellulare than between clarithromycin–amikacin. Clarithromycin is more promising than azithromycin as part of a therapy regimen against M. intracellulare infection. Abstract: Objectives: This study compared the in vitro synergistic effect between clarithromycin or azithromycin in combination with amikacin against Mycobacterium intracellulare . Methods: In vitro antimicrobial susceptibility of M. intracellulare isolates was determined by the broth microdilution method in cation-adjusted Mueller–Hinton broth. The fractional inhibitory concentration index (FICI) was also calculated to assess synergy between the antimicrobial agents. Results: A total of 32 respiratory M. intracellulare isolates were included in the study. Clarithromycin was the most potent agent against M. intracellulare, with MIC50 and MIC90 values (minimum inhibitory concentration required to inhibit 50% and 90% of the isolates, respectively) of 0.5 μg/mL and 8 μg/mL, respectively. Azithromycin and amikacin also showed moderate activity against M. intracellulare, with MIC90 values of 16 μg/mL and 4 μg/mL, respectively. The percentage of resistant strains among the 32 M. intracellulare isolates was 3.1% for clarithromycin, 9.3% for amikacin and 12.5% for azithromycin. The presence of amikacin had no effect on the MIC50 of clarithromycin, whereas the presence of amikacin resulted in a two-fold increase in the MIC50 of azithromycin. In addition, antagonism for the clarithromycin–amikacin combination was noted in 5 (15.6%) of the 32 M. intracellulare isolates, which was significantly lower than for the azithromycin–amikacin combination (14/32; 43.8%) ( P = 0.042). Conclusion: These data demonstrated that clarithromycin displayed more potent in vitro activity against M. intracellulare isolates than azithromycin. In addition, the antagonistic effect between azithromycin and amikacin was more frequent in M. intracellular isolates than that between clarithromycin and amikacin.